Application of Design Thinking Method in Developing Website-Based Balanced Fertilizer Usage Information System - Subhan A. Gani; Khairul Anshar; Syamsul Bahri; Syukriah; M. Saptariawan (LPPM Universitas Malikussaleh, 2022)
At this time the use of fertilizers is very important to increase plant productivity, but the use of fertilizers that are not in accordance with the needs of plants can affect the environment and the plants themselves due to improper use of fertilizers. After a survey conducted to farmers in North Aceh Regency, 90 percent of the 30 respondents surveyed did not know how to use balanced fertilizers. From these problems the author wants to develop website-based balanced fertilization information media that can be accessed anywhere via cellphone or laptop, in the development of information media using the Design Thinking method to design information media and using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) methods to test the website. The results of this study are the creation of website-based balanced fertilization information media that can answer the problems that occur and can help farmers get information, and the results of SUS testing get a performance value of 86.83 (Excellent), while UEQ testing gets a benchmark value above the average on 6 aspects with an Excellent value.